HUBUNGAN LEBAR KARAPAS DAN BERAT KEPITING BAKAU (Scylla spp.) DI PERAIRAN KAWASAN MANGROVE DESA JARING HALUS KABUPATEN LANGKAT SUMATERA UTARA - Raswin Nasution; Hesti Wahyuningsih; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
The Mangrove Crabs population is typically associated with good Mangrove forest, so habitat loss will have a serious impact on the Crabpopulation. One of the areas of Mangrove Crab catching in nature is theMangrove Area Waters of Jaring Halus Village. The purpose of this research was to know the relationship between the width of the carapace and the weight of theMangrove Crab (Scylla spp.) in Mangrove Waters of Jaring Halus Village,Langkat Regency, North Sumatera. This research was conducted in December 2016 - January 2017 with 3 catching stations using Bubu fishing equipment of 45 units. The catch was analyzed by simple linear regression W = a Lb. The number of Mangrove Crabs caught 178 heads consisting of 93 males and 85 females with sex ratio between male and female is 1 : 0,91. The carapace's width of caughtCaps ranged from 41 to 96 mm where the male carapace's width ranged from 41 - 90 mm, while the females ranged from 41 - 96 mm. Heavy Crab Mangrove that caught ranged from 30-540 mm where the males ranged from 30 - 370 grams while the female 30-540 grams. Growth of male and female mangrove crabs is positive allometric (b > 3) which means more dominant weight accretion compared to long accretion.Keywords: Jaring Halus Village, Mangrove, Scylla spp.